2005
DOI: 10.1128/jcm.43.7.3460-3462.2005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sensitivity of Sputum Smear Microscopy after Processing Specimens with C 18 -Carboxypropylbetaine To Detect Acid-Fast Bacilli: a Study of United States-Bound Immigrants from Vietnam

Abstract: The goal of this study was to evaluate the effect of the specimen-processing method that uses the detergent C 18 -carboxypropylbetaine (CB-18) on the sensitivity of acid-fast bacillus (AFB) staining. Vietnamese immigrants with abnormal chest radiographs provided up to three sputum specimens, which were examined for acid-fast bacilli by use of direct auramine and Ziehl-Neelsen staining. The remaining sputum was split; half was cultured, and the other half was incubated with CB-18 for 24 h, centrifuged, and exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…7 Our results are in parallel with Charles G. thornton 1998, K. F. Laserson 2005. 12,6 It has been shown CB-18 improves the recovery of mycobacteria other than tuberculosis among human respiratory specimens and also among animal products such as milk. [12][13][14][15] In present study, on processing the direct AFB negative sputum samples (N=279) using LJ medium culture had displayed an improvement in the positivity of AFB to 28.3% (N=79) indicating culture as a gold standard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Our results are in parallel with Charles G. thornton 1998, K. F. Laserson 2005. 12,6 It has been shown CB-18 improves the recovery of mycobacteria other than tuberculosis among human respiratory specimens and also among animal products such as milk. [12][13][14][15] In present study, on processing the direct AFB negative sputum samples (N=279) using LJ medium culture had displayed an improvement in the positivity of AFB to 28.3% (N=79) indicating culture as a gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…All processed specimens were decanted, resuspended in the remaining supernatant backwash, and transferred to microscope slides for staining. 6 …”
Section: Cb18 Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Thus, there was posibility of false negative sputum microscopically. Another possibility is that we also couldn't exclude the possibility of AFB positive adult TB living in the same house and the possibility of transmission from adult TB living not in the same house.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In this regard, few studies reported that bleach method of concentration is cheaper and safer method for the detection of AFB. 5 There are very less comparison studies between the NALC-NaOH and bleach methods of AFB concentration. So, a study has been designed to compare standard NALC-NaOH method with cheaper bleach method in resource limited settings.…”
Section: Introductionmentioning
confidence: 99%